Risk Spillovers and Required Returns in Capital Budgeting - Bhattacharyya, Sugato; Leach, J. Chris (Review of Financial Studies, 1999)
This article integrates strategic product market analysis with price-taking asset pricing theory. We demonstrate that a firm's market power can lead to scale-dependent and potentially infinite required returns. Scale dependency, which we relate to risk spillovers between expansionary and existing cash flows, reflects the divergence of incremental from existing required returns. The firm-specific nature of risk spillovers potentially destroys the concept of a common industry “risk class”. Our analysis raises important questions regarding the validity of widely used “comparables” methods for determining risk-adjusted discount rates.